ANALISIS WACANA KRITIS NORMAN FAIRCLOUGH PADA PEMBERITAAN GANJAR PRANOWO TENTANG PEMBELIAN PERTAMAX - ROSMALINA, IDA (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2023)
The Governor of Central Java, conducts inspection activities at gas stations to identify whether there are still people with economic conditions and above who still use subsidized fuel. The purpose of this research is the news from kompas.com and gridoto.com about the purchase of Pertamax or non-subsidized fuel at gas stations. The method used is descriptive qualitative, namely the data used is taken from news or literature study. The conclusion of this research is the analysis based on Norman Fairclgh's point of view consists of micro elements, namely theme, cohesion, coherence and lexical structure. Both mizzo elements have the production and distribution of news from both news portals such as kompas.com which are indeed based on social motives so that what happens is the system leads to a social focal point. The third is the macro element, consisting of situational and social levels. Based on the data analysis, the themes raised by the two news portals, namely kompas.com and Gridoto.com, the themes uploaded by Kompas.com focused more on the activities of officials or political elements who care about Pertamax BBM users, while gridoto.com focuses more on automotive or car users. luxury that uses pertalite. The Governor of Central Java is evidence of officials who care and have the awareness to prioritize social care for government regulations, namely the use of subsidized fuel.